Student development in college theory, research, and practice - Evans, Nancy J. 1947-; Forney, Deanna S. 1947-; Guido, Florence M.; Patton, Lori D.; Renn, Kristen A. (Jossey-Bass higher and adult education series, 2010)
The second edition of Student Development in College offers higher education professionals a clear understanding of the developmental challenges facing today's college students. Thoroughly revised and updated, this edition includes new integrative theories of student development, expanded coverage of social identity theories, a targeted focus on higher education-related research, a current review of student development research and application, and reconceptualization of typology theories as a way to understand individual differences.